Surgical management of recurrent oral submucous fibrosis (a collagen metabolic disorder due to the continuation of habitual factor) by split thickness skin graft from thigh: A clinical challenge - Karthik Shunmugavelu; Kumaravel Subramaniam (Wolters Kluwer Medknow Publications, 2016)
Usage of betel quid with areca nut is commonly seen in South Asian population. Most important premalignant condition, oral submucous fibrosis, arises due to this habit. The pathognomonic feature is characterized by higher intensity of submucosal collagen, inflammatory process, and palpable fibrotic bands intraorally, restricting the mouth opening. Management of this condition is of either medical or surgical means. Various grafts in surgical method are palatal island flaps, temporalis muscle flap graft, split-thickness skin graft, buccal fat pad graft, bilateral nasolabial flap, and tongue flap. Most serious complication of oral submucous fibrosis is oral carcinoma. Common site of involvement is of buccal mucosa which sometimes might extend up to pharynx. In our case report, we present a 35-year-old male with oral submucous fibrosis, previously treated by buccal fat pad and coronoidectomy, which recurred due to habits, currently managed by split-thickness graft from thigh. Postoperative outcome was good.